Foreign Experiences of Attracting Foreign Direct Investments (The Peerian Journal, 2023)
The essence of foreign direct investments is illuminated in the article. Also, the experiences of the USA and China in attracting foreign direct investments are explored. Special attention is being paid to effective use of production areas and facilities of state property and state-owned economic companies in the scientific research of the world’s countries to attract foreign direct investment, creation of favorable conditions for active investment attraction, further support for new competitive production and development of small enterprises special attention is paid